Introduction to the special issue on ability beliefs and learning a new language at school - Quint Oga-Baldwin, W. L.; Fryer, Luke K. (Studies in Second Language Learning and Teaching, 2025)
This editorial introduces a special issue examining ability beliefs in language learning psychology. The issue presents diverse theoretical perspectives on how learners’ perceptions of their abilities affect language acquisition outcomes. Drawing on foundational work in competence motivation, the collection addresses a critical gap in language education research by highlighting how ability beliefs – from self-efficacy to mindsets – serve as essential mediators between learning experiences and achievement. Contributors explore methodological considerations for causal inference, systematic reviews of key constructs, and frameworks integrating individual and ecological perspectives. We argue that ability beliefs contribute unique variance to language learning achievement, often eclipsing other psychosocial variables, yet remain underrepresented in prominent language learning theories. By clarifying these overlapping but distinct constructs, the special issue provides a foundation for more integrated theoretical models through rigorous empirical testing. This collection helps bridge psychological qualia with observable learning outcomes, pushing the field toward improved theoretical parsimony and practical relevance.